2013
DOI: 10.1590/s1415-47572013000300004
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the progress of colon cancer by DNA methylation markers of the p16 gene in feces - Evidence from an animal model

Abstract: A new noninvasive screening tool for colorectal neoplasia detects epigenetic alterations exhibited by gastrointestinal tumor cells shed into stool. There is insufficient existing data to determine temporal associations between colorectal cancer (CRC) progression and aberrant DNA methylation. To evaluate the feasibility of using fecal DNA methylation status to determine CRC progression, we collected stool samples from 14 male SD rats aged six weeks, and administered subcutaneous injections of either 1,2-dimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The development of an acceptable protocol could help in the study of the methylation status of tumor suppressor genes; their distribution in promoter regions; their distribution in the proximal colon, distal colon, and rectum; and their time sequence dependence in healthy individuals, particularly in those who develop CRC. Wu et al used an animal model to simulate the methylation status of the adenoma-carcinoma sequence, which is a precursor of animal cancer progression; but they did not study humans 18 . Finally, the results of the present study should be carefully interpreted because of the small number of patients who were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of an acceptable protocol could help in the study of the methylation status of tumor suppressor genes; their distribution in promoter regions; their distribution in the proximal colon, distal colon, and rectum; and their time sequence dependence in healthy individuals, particularly in those who develop CRC. Wu et al used an animal model to simulate the methylation status of the adenoma-carcinoma sequence, which is a precursor of animal cancer progression; but they did not study humans 18 . Finally, the results of the present study should be carefully interpreted because of the small number of patients who were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that methylation of cyclin-dependent kinase inhibitor 2A (CDKN2A), O-6-methylguanine DNA methyltransferase (MGMT) and human mutL homolog 1 (hMLH1), correlated with carcinogenesis pathways through gene silencing, could serve as diagnostic prognostic markers for CRC [14][15][16][17] . We selected two other candidate genes, colony stimulating factor 2 (CSF2) and DIS3 mitotic control homolog (S. cerevisiae)-like 2 (DIS3L2), from a previous study database 18 that involved inhibitory effects on tumor growth [19][20][21][22] . To understand the effect of specific gene methylation on the relationship between CRC prognosis including progression and mortality and histological stage, we explored DNA methylation status in tumor and adjacent normal tissues (matched normal) from subjects who received surgical resection for CRC.…”
mentioning
confidence: 99%